Origins and Stepwise Expansion of R2R3-MYB Transcription Factors for the Terrestrial Adaptation of Plants - Chang, Xiaojun; Xie, Shupeng; Wei, Lanlan; Lu, Zhaolian; Chen, Zhong-Hua; Chen, Fei; Lai, Zhongxiong; Lin, Zhenguo; Zhang, Liangsheng (Frontiers in Plant Science, 2020)
The R2R3-MYB transcription factors play critical roles in various processes in embryophytes (land plants). Here, we identified genes encoding R2R3-MYB proteins from rhodophytes, glaucophytes, Chromista, chlorophytes, charophytes, and embryophytes. We classified the R2R3-MYB genes into three subgroups (I, II and III) based on their evolutionary history and gene structure. The subgroup I is the most ancient group that includes members from all plant lineages. The subgroup II was formed before the divergence of charophytes and embryophytes. The subgroup III genes form a monophyletic group and only comprise members from land plants with conserved exon-intron structure. Each subgroup was further divided into multiple clades. The subgroup I can be divided into I-A, I-B, I-C, and I-D. The I-A, I-B, and I-C are the most basal clades that have originated before the divergence of Archaeplastida. The I-D with the II and III subgroups form a monophyletic group, containing only green plants. The II and III subgroups form another monophyletic group with Streptophyta only. Once on land, the subgroup III genes have experienced two rounds of major expansions. The first round occurred before the origin of land plants, and the second round occurred after the divergence of land plants. Due to significant gene expansion, the subgroup III genes have become the predominant group of R2R3-MYBs in land plants. The highly unbalanced pattern of birth and death evolution of R2R3-MYB genes indicates their important roles in the successful adaptation and massive radiation of land plants to occupy a multitude of terrestrial environments.